Soft Semi-Norm Spaces &Soft Pseudo Metric Spaces - H. Radhi, Intisar (Al-Qadisiyah Journal of Pure Science, 2018)
The paper introduces definitions for some properties of the soft set as balanced, absorbing and convex. The study discusses a number of theorems and observations about these properties. A definition for soft semi-norm space is introduced. The paper also proves one of the soft pseudo metric space axioms which are introduced by [7]. It discusses some of the propositions and theories related to the two spaces. A theory that explains the relation between the two spaces is introduced.